The prognostic significance of (18F)FDG PET/CT in multiple myeloma according to novel interpretation criteria (IMPeTUs) - Sachpekidis, Christos; Merz, Maximilian; Raab, Marc-Steffen; Bertsch, Uta; Weru, Vivienn; Kopp-Schneider, Annette; Jauch, Anna; Goldschmidt, Hartmut; Dimitrakopoulou-Strauss, Antonia (EJNMMI Research, 2021)
Purpose: [18F]FDG PET/CT is the elective imaging modality for treatment monitoring in multiple myeloma (MM). However, MM is a heterogeneous disease from an imaging point of view, raising challenges in interpretation of PET/CT. We herein investigated the prognostic role of the novel Italian Myeloma criteria for PET Use (IMPeTUs) in MM patients undergoing high-dose chemotherapy (HDT) followed by autologous stem cell transplantation (ASCT). Methods: Forty-seven patients with newly diagnosed MM underwent [18F]FDG PET/CT before commencement of treatment (baseline PET/CT). Thirty-four of them (72.3%) were also examined after completion of ASCT (follow-up PET/CT). PET/CT analysis was based on the IMPeTUs criteria, which take into consideration—among others—the metabolic state of the bone marrow based on the 5-point Deauville score (DS), the number and metabolic state of focal [18F]FDG-avid lesions, as well as the presence of paramedullary disease (PMD) and extramedullary disease (EMD). We analyzed whether parameters from IMPeTUs correlate with clinically relevant parameters and patients’ outcome, as assessed by progression-free survival (PFS). Results: Median follow-up from baseline and follow-up PET/CT were 85.1 months and 76.7 months, respectively. The number of focal, [18F]FDG-avid lesions significantly correlated with the bone marrow infiltration rate and the R-ISS stage, while the presence of PMD was associated with LDH. After univariate survival analysis, the number of focal, [18F]FDG-avid lesions both before and after therapy as well as the presence of PMD and EMD before therapy adversely affected PFS. Multivariate survival analysis for baseline parameters confirmed that the number of focal, [18F]FDG-avid lesions and the presence of EMD are associated with adverse prognosis, irrespective of the ISS stage and/or the presence of high-risk cytogenetic abnormalities. The 5-point DS of [18F]FDG uptake in reference bone marrow and focal lesions showed a significant decrease as response to treatment, but it did not affect PFS. Conclusion: Several parameters utilized in IMPeTUs predict PFS in MM patients, suggesting the potentially significant role of the new criteria in patient stratification and response assessment. Additional studies are warranted for the further evaluation of IMPeTUs in the direction of establishment of robust cut-off values with a prognostic significance in the disease.
Gesehen am 22.11.2021
Im Titel ist die Zahl 18 hochgestellt
Im Titel ist der Ausdruck "18F" eckig geklammert